Navigating the internet use as the encounter of the new literacy studies for periphery EFL teachers: A critical self-reflection - Wahyudi, Ribut (Journal of Research, Policy & Practice of Teachers and Teacher Education, 2018)
The internet has been an integral part for most EFL teachers nowadays. Those teachers make use of the internet to help them at least search for appropriate materials for their classroom teaching. Some others use the internet to discuss particular courses outside the classroom time. However, the fact that the internet has been of central use, the research on it in relation to literacy (read, write, research and publish) for EFL teacher personal and professional development in developing countries is under explored (Warschauer, Shetzer and Meloni, 2002, cited in Cahyani & Cahyono, 2012). In that regard, this article is to address that critical issue. As an EFL teacher from the developing country myself, my personal and professional experiences and my encounters with colleagues on the internet use inform my subjectivities in writing this article. As the current globalized world requires teachers to have multi-literacy skills, I deliberately frame the internet use within New Literacy Studies (NLS) which sees literacy as social practice (Street 1985 cited in Street, 2003), an event and set of practices, a global and local practice, faith based and critical (Pahl & Rowsell, 2012). The foci of my discussion will be on the use of internet for the sake of teaching resources, research purposes, expansion of social network and professional development.